DIPLOMASI INDONESIA DALAM MEMPROMOSIKAN PARIWISATA DI THAILAND 2015 - 2018 - Annisa Maulidina, (2020)
This research analize about diplomacy to promoting tourism in Thailand in 2015 untill 2018. This research is a qualitative research. The method of data collection used in this study using the method of study document, study of the literature and interviews. Research methods using primary and secondary data retrieval. The method of analysis used in this study is qualitative data analysis techniques. In theory, diplomacy by Indonesia is to form a positive image of Indonesia tourism to Thai people in order to attract tourist from Thailand to visit Indonesia. Therefore public diplomacy is a theory used in this study. In addition, the concept of Multi-track diplomacy is also used to explain who is involved in this diplomacy because this diplomacy is not only through by stateactors but also non-state actors. The results of this research indicate that Indonesia's diplomacy efforts to promote tourism in Thailand have been effectively because it has succeeded in increasing the number of Thai tourists visiting Indonesia.